EMISI METHANA (CH4) DARI SALURAN DRAINASE LAHAN GAMBUT DI KALIMANTAN TENGAH - Eni Yulianingsih (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2016)
ABSTRACTPeatland development is increasingly becoming a strategic, both in terms of aspects of agronomy, and environmental aspects. Information magnitude of GHG emissions from drainage canals are important in the management of peat sustainability. Its objective is to determine the amount of GHG emissions from peatland drainage channels that are used for traditional rubber plantation. Gas sampling is done in the secondary drainage channel with a channel width of 5 m and 3 m wide tertiary. Sampling was performed six times with five points by using the lid closed cylinder. Sample was analyzed by gas chromatography flame ionization detector incorporates detector (FID) for the determination of the concentration of CH4. CH4 fluxes in peatland drainage channel width of 5 m is relatively higher than in the drainage channel width of 3 m in Jabiren peatlands of Central Kalimantan. GHG emissions in the channel width of 5 m was 542,20 ± 258,57 kg CO2-e yr-1 and 379,14 ± 260,7 kg CO2-e yr-1 of the channel width of 3 m.